Research of double-threshold spectrum sensing algorithm based on D-S theory - WANG Meng-dong; CHEN Xiang; GUAN Yu; XIAO Shu-yan (Gong-kuang zidonghua, 2013)
In view of problem that traditional double-threshold spectrum sensing algorithm cannot make full use of information of sensing users between two thresholds, the paper proposed a double-threshold spectrum sensing algorithm based on D-S theory. When signal energy received by the sensing users lies between the two thresholds, the algorithm does not give judging result directly but makes local judgment, namely it uses D-S theory to make data fusion. Simulation result shows that detection probability of double-threshold spectrum sensing algorithm based on D-S theory is higher than one of the traditional double-threshold spectrum sensing algorithm, which improves performance of spectrum sensing.